1971
DOI: 10.1063/1.1675086
|View full text |Cite|
|
Sign up to set email alerts
|

Light Scattering and the Coupling of Molecular Reorientation and Hydrodynamic Modes

Abstract: Distribution of reorientational times of optically anisotropic molecular liquids from depolarized lightscattering studiesA statistical theory, based on linear response theory, is presented to describe the coupling between molecular reorientation and both longitudinal and shear hydrodynamic modes in liquids, and the effect of this coupling on the depolarized light scattering spectrum. The theory is valid if molecular reorientation takes place by rotational diffusion. The "doublet" features of the observed spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

1973
1973
2015
2015

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(49 citation statements)
references
References 17 publications
1
48
0
Order By: Relevance
“…The original papers of Keyes and Kivelson [6] and of Andersen and Pecora [7] were the first to propose a twovariable theory which could explain the existence of the Rytov dip at high temperature and its change into propagative transverse modes at lower temperatures. They did not make use of an equation of motion for the mass current density (Eq.…”
Section: Equations Of Motion In the Two-variable Theories Without Retmentioning
confidence: 99%
See 3 more Smart Citations
“…The original papers of Keyes and Kivelson [6] and of Andersen and Pecora [7] were the first to propose a twovariable theory which could explain the existence of the Rytov dip at high temperature and its change into propagative transverse modes at lower temperatures. They did not make use of an equation of motion for the mass current density (Eq.…”
Section: Equations Of Motion In the Two-variable Theories Without Retmentioning
confidence: 99%
“…Both Keyes and Kivelson [6] and Andersen and Pecora [7] used, for the additional variable which has to enter into the stress tensor associated with Π ij (σ ij = −Π ij ) a symmetrical 2nd rank tensor which was assumed to describe a polarizability density (or, more accurately, the traceless part of the fluctuation of such a quantity). In order to write down the corresponding equations of motion, they made use of the Zwanzig-Mori formalism, introducing the symmetry properties of the correlation functions of this variable and of the momentum density rather than writing the explicit form of σ ij (r, t).…”
Section: Hydrodynamic Equationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Extensive studies of generalized collective modes [21,22] showed a convergence of the GCM eigenvalues with systematic extension of the set of dynamic variables up to the third time derivatives of the hydrodynamic ones. The GCM methodology is very close to the generalized hydrodynamic theory by Kivelson and Keyes [23,24] developed for molecular fluids. The microscopic theory of extended collective modes enables correct description of the hydrodynamic modes as well as of the well-defined short-wavelength collective excitations for large wave numbers [25,26].…”
Section: Extended Hydrodynamic Approachmentioning
confidence: 98%